Pengaruh Ukuran Perusahaan dan Profitabilitas Terhadap Nilai Perusahaan - Eka Indriyani (Department of Accounting-Faculty of Economic and Business (FEB), 2017)
The population in this study is all companies manufacturing food and beverage sectors in Indonesia Stock Exchange period 2011 to 2015. The study sample as many as 16 companies were selescted using purposive sampling method with certain criteria in order to obtain in the total sample 0f 9 companies. Mechanical testing of the data is by using multiple linear regression with a significance level of 5% alpha. The results showed that firm size negative effect on firm value. Profitability significant effect on firm value. Simultaneously, firm size and profitability significantly influence the value of the company. The coefficient of determination shows that the influence of the independent variables on the dependent variable of 41.5% and the rest is influenced by other factors.